PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS KARAKTER TERHADAP HASIL BELAJAR SISWA KELAS IV MATERI KEBERAGAMAN SOSIAL BUDAYA di SDN 2 BABAKTULUNG - Siti Khoironnisa; Ifa Seftia Rakhma Widiyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low student comprehension of the topic of Social and Cultural Diversity at SDN 2 Babaktulung has posed a significants obstacle in the teacing of Pancasila Educations. This issue is primarily due to the limited use of innovative learning media and the contiuned reliance on conventional, textbook-based teaching methods. To address this problem, this study aims to develop a character-based instructional video to improve the learning outcomes the research aimed to strengthen the comprehension of fourth-grade students regarding the topic by employing the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data were colledted through observation, interviews, expert validations, pretests and posttests. Quantitative data were analyzed using Likert scale, n-Gain, and Guttman scale, while qualitative data were obtained from feedback and implementation observations. The result show that the developed instructional video achieved high validity, with experts validation score of 93% content, language experts (88%), media experts (83%), and practitioners (81%). The media also demonstrated high effectiveness, with an n-Gain score of 0,7. Furhermore, the readability test showed a score of 97%, while practicality was rated at 94% by students and 100% by the theacher. These findings indicate that the character-based instructional video is a practical and effective toll for enhacing student understanding of social and cultural diversity.